Visceral Leishmaniose: epidemiological and temporal analysis in the state of Maranhão, Brazil (Research, Society and Development, 2020)
Visceral Leishmaniasis (VL) is a chronic evolutionary zoonosis, caused by a protozoan of the species Leishmaniachagasi, with systemic involvement and, if left untreated, can lead to death in up to 90% of cases. The State of Maranhão, since 1982, appears as one of the protagonists regarding the number of cases of this infection in Brazil. This study aimed to delineate the epidemiological profile of cases of Visceral Leishmaniasis, reported in Maranhão, retrospectively, from 2007 to 2017. A descriptive study was conducted from the database available at the Center for Information and Analysis in SUS (DATASUS), through the National System of Notification of Disorders (SINAN). A total of 6,112 reported cases were analyzed through exposure of quantitative variables. Where it was perceived that, as belonging to the group of diseases considered neglected, VL can have negative impacts on public health, mainly in endemic areas. Thus, it needs studies that stimulate and guide health actions, for the benefit of society.